Reporting pH-sensitive drug release via unpaired spin fluorescence silencing. Issue 4 (10th January 2018) - Eing, Matthias; Olshausen, Bettina; Fairfull-Smith, Kathryn E.; Schepers, Ute; Barner-Kowollik, Christopher; Blinco, James P.
Abstract : We pioneer an approach for the visualization of a self-reporting pH-controlled molecular release of a fluorescent drug from a nitroxide polymer scaffold. Abstract : We pioneer an approach for the visualization of pH-controlled molecular release of a fluorescent drug from a nitroxide polymer which combined yields a profluorescent system. A methacrylate-based terpolymer, bearing water-solubilizing triethylene-glycol chains, unpaired spins in the form of nitroxide and hydrazone-bound doxorubicin was synthesized to explore the possibilities of release quantification from profluorescent assemblies. Critically, we establish the fluorescence-silencing effect of polymer-bound nitroxides on covalently attached fluorophores and the overall accessibility of such constructs. The facile approach towards a functional assembly shown here provides an easy-to-assemble construct for complex delivery architectures towards applications in theranostics.